The mediating role of leader-member exchange on the relationship between employee motivation and interpersonal citizenship behaviour among administrative officers in Malaysian public universities / Shereen Noranee - Noranee, Shereen (Institute of Graduate Studies, UiTM, 2016)
Interpersonal citizenship behaviour is a discretionary behaviour, beyond employee job requirements, that supports coworkers and/or supervisors. It requires a relationship between an interpersonal citizenship performer and a receiver in which the performer voluntarily provides benefits to the receiver as an ingredient of the behaviour. Employees who perform interpersonal citizenship behaviour are not only prosocially-motivated but also are motivated by impression management. The level of the behaviour may vary based on the relationship with their supervisors. This study examines the mediating effect of leader-member exchange relationship towards the relationship between prosocial motivation and impression-management motivation. The public university administrative officers. Sets of questionnaires were used to collect data about employee interpersonal citizenship behaviour, employee motivation, and leadermember exchange relationship. The respondents were 210-dyads, which comprised of subordinates and immediate supervisors, from 20 public universities in Malaysia. The result shows that prosocial and impression-management motivation were related to self-rating leadermember exchange, while prosocial motivation had a negative effect on supervisor-rating leader-member exchange quality relationship…